Combustion characteristics and energy distribution of hydrogen engine under high oxygen concentration. (1st November 2022) - Fu, Hongyu; Luo, Qinghe; Bao, Lingzhi; Sun, Baigang; Niu, Qingyu; Zhang, Shiwei; Zhang, Hao
Abstract: Integrated Vehicle Fluid (IVF) system is a promised energy management system for cryogenic upper stage. The power unit of IVF is hydrogen-oxygen internal combustion engine (ICE) whose energy utilization is close to 100% in IVF system. The oxygen concentration of intake gas was gradually raised during ICE tests as a preliminary study. The power of hydrogen-oxygen ICE reaches 4 kW at 3000 r/min, which satisfies the power requirement of IVF system. At this time, the exhaust loss reaches 41.6%, the heat transfer loss is 35.9%, and the output power only accounts for 21.9%. The heat transfer loss shows a parabolic trend which first rises and then falls with increasing oxygen concentration. But the exhaust loss keeps growing with the increases in oxygen concentration and engine speed. It is significant for the design of regenerative cooling system and other subsystems in IVF system at specific engine speed. Highlights: Engine tests under 21%, 30% and 40% oxygen concentration were performed. Laminar burning velocities of hydrogen under high oxygen concentration were studied. One-dimensional simulation of engine was performed under higher oxygen concentration. Energy of each part under different oxygen concentration were analyzed in detail.